Effects of a nutrition education intervention on nutrition knowledge and attitude among overweight and obese primary schoolchildren: a cluster randomized controlled trial - Rusidah Selamat; Nur Azlina Abdul Aziz; Junidah Raib; Norlida Zulkafly; WNurul Ashikin W. Mohamad; Ainan Nasrina Ismail; Muhammad Yazid Jalaludin; Fuziah Md. Zain; Zahari Ishak; Abqariyah Yahya; Abdul Halim Mokhtar (BMC Public Health)
Abstract Background School-based obesity interventions are a promising strategy for combating childhood obesity. In this study, we examined the efficacy of the “My Body is Fit and Fabulous at School” (MyBFF@school) program with a nutrition education intervention (NEI) for improving nutrition knowledge and attitude among overweight and obese primary schoolchildren. Methods A school-based cluster randomized controlled trial of the MyBFF@school obesity intervention program was conducted among overweight and obese schoolchildren aged 9–11. Out of 1,196 eligible government primary schools in central Peninsular Malaysia, 23 were randomly assigned into seven intervention schools (647 children) and 16 control schools (750 children). A standard nutrition education module was delivered for 24 weeks to the intervention group, whereas children in the control group followed only the currently existing school nutrition education program. The main outcome measures were nutrition knowledge and attitude scores. Changes of nutrition knowledge and attitude scores from follow up until end of 6 months was assessed using the mixed effect model taking into account the cluster effect. Results A total of 563 children in the intervention group and 482 in the control group completed the six-month program and were included in the analysis. The overall nutrition knowledge score was significantly higher in the intervention group (adjusted mean difference (AMD): 4.75%, $$p=0.028$$ p = 0.028 ) after controlling for mean nutrition knowledge score at baseline, gender, location school group (intervention vs control) and ethnicity. There was also a significant improvement in the nutrition knowledge score with AMD among boys (6.02%), urban children (8.07%), and non-Malays (10.4%). In contrast, after controlling for mean nutrition attitude score at baseline, gender, location, school group (intervention vs control) and ethnicity, there was no significant difference in the nutrition attitude scores between the intervention and the control groups in the overall, gender, location and ethnicity. Conclusions The MyBFF@school program with an adjunct NEI improves the overall knowledge on nutrition but has no positive effect on the nutrition attitude of younger schoolchildren, necessitating additional improvements. Trial registration Clinical trial number: NCT04155255, November 7, 2019 (Retrospective registered). National Medical Research Register: NMRR-13–439-16563. Registered July 23, 2013. The intervention program was approved by the Medical Research and Ethics Committee (MREC), Ministry of Health Malaysia and Educational Planning and Research Division (EPRD), Ministry of Education Malaysia. It was funded by the Ministry of Health Malaysia.